Faktor-Faktor yang mempengaruhi Kadar hemoglobin ibu hamil di Puskesmas Rappokalling Makassar - Nurana, Sitti (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Indonesia is one of the countries with the highest MMR in Asia and the 3rd highest in the ASEAN region. MMR in Indonesia, the 2015 SUPAS results were 305/100,000 live births. Pregnant women are declared anemic if hemoglobin (Hb) < 11 mg/L (1) . The Ministry of Health (2005) states that the impact that causes anemia in pregnant women is bleeding during childbirth, low birth weight (LBW) babies, suboptimal IQ, babies easily infected and easily suffering from malnutrition. Hemoglobin concentration and hematocrit during pregnancy. This study aims to determine the factors that influence the HB levels of pregnant women at the Rappokalling Health Center, Makassar. The factors that will be studied are direct factors, namely compliance with consuming Fe tablets and the nutritional status of pregnant women. During pregnancy the plasma increases quite large so the concentration of hemoglobin and hematocrit decreases somewhat, during pregnancy the overall blood viscosity decreases, the average hemoglobin concentration at term is 12.5 g/dl, and in around 5% of women the concentration is less than 11.0 g/dl. dl, therefore a hemoglobin concentration below 11 g/dl, especially at the end of pregnancy should be considered abnormal and is usually caused by iron deficiency and not due to hypervolemia of pregnancy. This research was carried out at PUSKESMAS Rappokalling Makassar, with the sampling technique being non-probability sampling with accidental sampling, namely the sampling method carried out by chance meeting, the sample in this study was 103 respondents from pregnant women. The results showed that there was a significant relationship between mothers' compliance with consuming Fe tablets and the Hb levels of pregnant women at the Rappokalling Health Center in Makassar. There was a significant relationship between the nutritional status of pregnant women and the Hb levels of pregnant women at the Rappokalling Health Center in Makassar.